Portable & Smartphone Spectroscopy for Food Adulteration (Journal of Food and Dietetics Research, 2026)
Ensuring food quality, safety, and authenticity has become increasingly critical due to the growing complexity of global  food supply chains and the rising incidence of food adulteration. Rapid technological advancements have significantly  enhanced the ability to authenticate food products and detect fraudulent practices. Traditional food authentication  approaches primarily relied on the assessment of a limited number of indicators against predefined standards. In con trast, modern analytical strategies employ targeted profiling and untargeted fingerprinting techniques that integrate  advanced spectroscopic methods with sophisticated statistical analyses, enabling more accurate and reliable detection of  adulteration. Although several reviews have examined conventional spectroscopic techniques and general food authen tication methods, limited attention has been given to the emerging field of portable and smartphone-based spectroscopy.  The increasing availability of smartphone-integrated analytical platforms offers new opportunities for rapid, cost-effec tive, user-friendly, and on-site food analysis. Therefore, a comprehensive evaluation of these technologies is timely and  necessary. This review explores the application of smartphone-assisted spectroscopic technologies for food adulteration  detection. It discusses the integration of smartphones with spectroscopic systems, smartphone-based biosensors, fluo rescence spectroscopy, and colorimetric approaches for food quality assessment. Recent smartphone spectroscopy plat forms and their analytical performance are critically summarized, highlighting advances in portability, sensitivity, and  real-time monitoring capabilities. Furthermore, the review also examines current challenges, technological limitations,  and future market prospects for smartphone-enabled food analysis. By providing a focused and updated assessment of  recent developments, this review addresses gaps in previous literature and highlights the potential of smartphone-based  spectroscopy as an accessible and effective tool for food authentication and adulteration detection.
Keywords: Smartphone Spectroscopy; Food Adulteration Detection; Food Authentication; Portable Analytical Devices; Biosensors; Food Quality Assessment